Tucanogovea schusteri n. gen. n. sp., a new cyphophthalmid (Opiliones, Cyphophthalmi, Neogoveidae) from Amazonia - Karaman, Ivo (Biologia Serbica, 2014)
A new cyphopthalmid genus and species, Tucanogovea schusteri n. gen. n. sp., is described from Amazonas State, Brazil. The new genus clearly differs from other Neotropical neogoveids by the presence of a dorsal lobe on the spermatopositor, a so far unknown structure. The new genus is closely related to the genus Huitaca Shear, 1979. Genus Metasiro is proposed to be excluded - and the genus Shearogovea is proposed to be included into the family Neogoveidae. Characters from the spermatopositor structure arise as essential for neogoveid generic designations. A tendency of shifting of the male gonostome anteriorly toward the posterior line of coxal lobes III is sugested as a synapomorphic character of the family Neogoveidae.